(untitled) (European Journal of Interdisciplinary Studies, 2020)
Oral and dental health services in Turkey is open to international competition and a rapidly growing sector within the scope of health tourism. It is very important to maintain patient satisfaction and patient loyalty in service delivery. It is known that patient and patient relatives care about attitudes and behaviors of health workers and this experience is effective in the choose of physicians or health institutions. The aim of this study is to determine the intercultural sensitivity and communication competencies of employees in a private oral and dental health clinic in Denizli which is one of the most important tourism centers of Turkey. In this study, the Intercultural Sensitivity Scale, in which individuals evaluated themselves, was used to measure intercultural sensitivity. This scale, which was developed by Chen and Starosta (2000) and included five emotional dimensions required to be sensitive to interculturalism, was translated into Turkish by Kurban et al. (2011) and evaluated the psychometric suitability. Communication Competence Scale, which was developed by Wiemann (1977) and translated into Turkish, validity and reliability of the communication competence by Koca and Erigüç (2017) was used. Data were collected online via Google docs during January and February 2019. According to the findings of the study, it was observed that the intercultural sensitivity and communication competencies of the health workers were high and the highest score was the enjoyment of communication dimention (4.10±0.74) in the scale of intercultural sensitivity and the compliance adequacy dimention (4.13±0.97) in the communication competence scale.